2021
DOI: 10.1073/pnas.2019768118
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide detection of cytosine methylation by single molecule real-time sequencing

Abstract: 5-Methylcytosine (5mC) is an important type of epigenetic modification. Bisulfite sequencing (BS-seq) has limitations, such as severe DNA degradation. Using single molecule real-time sequencing, we developed a methodology to directly examine 5mC. This approach holistically examined kinetic signals of a DNA polymerase (including interpulse duration and pulse width) and sequence context for every nucleotide within a measurement window, termed the holistic kinetic (HK) model. The measurement window of each analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
72
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 34 publications
0
72
0
2
Order By: Relevance
“…2) For the PacBio sequencer, Tse et al developed a method to detect 5 mCs using SMRT sequencers [75] . This algorithm is based on the difference in inter-pulse duration and pulse width between methylated and unmethylated cytosine.…”
Section: Dna Methylation and Svsmentioning
confidence: 99%
“…2) For the PacBio sequencer, Tse et al developed a method to detect 5 mCs using SMRT sequencers [75] . This algorithm is based on the difference in inter-pulse duration and pulse width between methylated and unmethylated cytosine.…”
Section: Dna Methylation and Svsmentioning
confidence: 99%
“…Thus, PacBio sequencing misses the m5C methylase activities ( 2 ) unless the 5-methylcytosine detection is enhanced by treating the library with Ten-eleven translocation enzyme ( 6 ). A recent study uses a holistic kinetic model to identify m5C using PacBio reads ( 7 ). Nonetheless, methylation can only be identified in CpG context, restricting the use of this approach to organisms such as human, for which methylation is almost exclusively in CpG sites.…”
Section: Introductionmentioning
confidence: 99%
“…Sequencing technologies such as Oxford Nanopore technology (ONT) single-molecule real-time (SMRT), whole genome bisulfite sequencing (WGBS), or NEBNext Enzymatic Methyl-seq platforms have made available mapping three of the dominant features in prokaryotic methylomes [18][19][20]. No one method is the perfect tool, biases towards low CG content, over representation of methylation fraction, precision, organism of study, and indels can be found to varying degrees within each platform [21][22][23][24][25][26]. The three typically studied genomic methylation forms are N6-methyladenine (6 mA), N4methylcytosine (4mC), and 5-methylcytosine (5mC) [27,28].…”
Section: Introductionmentioning
confidence: 99%